GANDHI’S APPROACH TO WOMEN’S LIBERATION - Pushparajan, A. (Journal of Dharma, 1988)
Many reformers before Mahatma Gandhi had struggled hard for the liberation of women in India. Raja Ram Mohun Roy (1772-1833), Swami Dayananda Saraswathi (1827-1883), Justice Mahadev Govinda Ranade (1842-1901), Swami Vivekananda (1862-1902), Gopala Krishna Gokhale (1866-1915), Rabindranath Tagore (1861-1941) are some of the pioneers in the cause of Women’s liberation in India. In addition to them, there were many women reformers who contributed to this cause. Pandita Ramabai (1858-1922), Ramabai Ranade (1865-1922), Anandibai Joshi (18651887), Francina Sorabji (1833-1910), Annie Besant (1847-1933) are some ofthe well-known illustrations.’ However, it remains an unquestionable fact that few have actually contributed more to the cause of women’s liberation than M. K. Gandhi. What then are the actual achievements of Gandhi in respect of women’s liberation? This is the question which crops up to any inquisitive mind. So, the first section of this article devotes itself to recount some of the most illustrious ways in which Gandhi espoused the women’s cause.